[PP.17.14] ASSOCIATION BETWEEN BLOOD PRESSURE VARIABILITY AND FUNCTIONAL OUTCOME IN DIFFERENT ISCHEMIC STROKE SUBTYPES. (September 2016) - Korompoki, E.; Gill, D.; Manios, E.; Vemmou, A.; Spengos, K.; Zakopoulos, N.; Vemmos, K.
Abstract : Objective: Blood pressure variability (BPV) has been associated with worse outcomes after acute ischemic stroke (IS). The aim of this study was to investigate whether this association varies in the in different IS subtypes. Design and method: A total of 239 consecutive first-ever acute stroke patients registered in the Athens Stroke Registry underwent 24-hour ambulatory BP monitoring (ABPM) within 24 hours of stroke onset. Strokes were categorized according to the TOAST classification. Functional outcome was measured at 3 months using the modified Rankin Scale (mRS), and was dichotomised to either good (mRS < or = 2) or poor (mRS > 2). BPV was defined as the standard deviation (SD) of blood pressure recordings made by ABPM. Stroke severity was measured using the National Institutes of Health Stroke Scale (NIHSS). Logistic regression analysis was used to test whether systolic or diastolic BPV predicted functional outcome, after adjusting for age, stroke severity and history of hypertension, diabetes, hyperlipidaemia and smoking. Coefficients and 95% confidence interval (CI) were used to indicate effect size; p < or = 0.05 was used to indicate statistical significance. Results: IS was attributed to small vessel disease in 64 cases, to large artery atherosclerosis (LAA) in 54 cases and to cardioembolism in 77 cases. The remaining 44 cases were classified as cryptogenic stroke or of unknown origin. The mean age of the study population was 69.3 (10.1) and 64% were males. The median NIHSS at admission was 5 (0–33) and median mRS at 3 months was 2 (0–6). Mean SBP and DBP at admission were 161 (28) mmHg and 90 (12) mmHg, respectively. The logistic regression analysis revealed that higher diastolic BPV was independently associated with poor functional outcome at 3 months only in lacunar strokes (coefficient 0.30, CI 0.99–1.72, p = 0.05). No significant association was observed between BPV and functional outcome in IS caused by LAA (p = 0.38) or cardioembolism (p = 0.38). Conclusions: Increased diastolic BPV 24 hours after lacunar IS is associated with worse functional outcomes at 3 months. Further work is required to reproduce this finding in an independent cohort, and to explore possible underlying mechanisms.